TIME MANAGEMENT ANALYSIS USING THE CPM METHOD ON DREAMLAND HOUSING DEVELOPMENT, BATAM - Ahmad Mawardi Lubis; A. Savitri (Racic : Rab Construction Research, 2025)
Time management is very necessary in a construction project. A project will be completed on time if you have good time management. The CPM method and PERT Network Diagram are methods that allow the work of a project to be completed in a shorter time by connecting work activities with each other. In this research, the author analyzes time management using the CPM method and PERT Network Diagram on a Dreamland housing development project in Batam. As a result, all work on this project will be completed in 340 days. Apart from that, the critical path is also obtained in this project. Work that is on the critical path must be given more supervision and attention in its implementation so that the project can be completed on time and there are no delays.